Citizen science mitigates the lack of distributional data on Nigerian birds - Tende, T.; Iniunam, I.; Ivande, S.T.; Awoyemi, A.G.; Danmallam, B.A.; Ringim, A.S.; Bako, L.A.; Ramzy, F.J.; Kazeh, N.W.; Izang, A.I.; Kumdet, P.S.; Ibrahim, J.I.; et al. (Wiley, 2024)
Citizen science projects are expanding globally, with the African continent, particularly Nigeria, registering significant growth. Here, we document and analyse novel operations of the Nigerian Bird Atlas Project (NIBAP), 2015--2022. This project has employed the use of ornithologists, mainly trained at the A. P. Leventis Ornithological Research Institute (APLORI) located in Jos, Nigeria, and its 28 bird clubs established across Nigeria to enlist 827 bird enthusiasts that contribute regular and near real-time data about bird distribution and relative abundance in the country. Interestingly, NiBAP has recorded about 75% of the bird species known from Nigeria in only about 50% of Nigeria's total surface area, including 39 nationally threatened species. The Common Bulbul *Pycnonotus barbatus*, Laughing Dove *Spilopelia senegalensis*, and Grey-backed Camaroptera *Camaroptera brevicaudata* were the most commonly recorded species, while Amurum Forest Reserve, Rennajj Fish Farm, and Obudu Cattle Ranch were the most surveyed sites during the period. Thus, our approach reveals how to increase involvement of nature enthusiasts, ornithologists, and a regional research institute to build local capacity and contribute rich information necessary to alleviate the lack of distributional data about Afrotropical avifauna. We strongly recommend our approach to boost other citizen science projects across Africa and beyond to address the huge lack of biodiversity data, create public awareness, and foster conservation education.